Legalizing premium secondhand trade: Economic potential for Bali’s tourism special economic zones - Akhmad Firdiansyah; Putu Tegar Pradiawan (WIM Solusi Prima, 2026)
This study analyzes the economic potential of legalizing the premium secondhand trade in Bali Province driven by tourist expenditures, utilizing the 2016 Tourism Satellite Account (TSA) framework and Input-Output (I-O) Table. A simulated shock of IDR 1.27 trillion was applied to the